The Klan - Sims, Patsy. frey50 (New York : Stein and Day, 1978)
The Klan lives. Its extent and vitality will surprise and dismay many readers. Ms. Sims attempts to take an objective look at the organization and its leaders and members in a series of profiles, with the history, news events, arrest records, and the experiences of law enforcement officials and victims woven in.
Keywords: Ku Klux Klan (1915- )